Animal welfare practices for bulls in semen stations - Biswas, Newton; Singh, Kiran; Srivastava, Neeraj (Indian Farming, 2024)
The concept of artificial insemination (AI) has revolutionized the livestock sector. The high-quality semen collected from genetically superior bulls is extended and preserved to artificially impregnate maximum numbers of breedable cows. Rearing bulls separately and solely for superior germplasm became integral to animal husbandry, especially for commercial dairy and meat industries. The set-up established for maintaining bulls for semen collection and processing for AI is known as a semen station. Although the animal husbandry norms ensure adequate treatment for bulls maintained in semen stations as far as their housing, feeding, deworming, vaccination, etc. are concerned, animal welfare standards are merely followed. The purpose of animal welfare is to ensure the humanetreatment of animals used for production. It is a proven fact that animal husbandry practices blended with animal welfare concepts not only boost the quantity but also ensure the quality of production. Therefore, adequate stress management, the use of modern technological tools such as artificial intelligence, and behavioural considerations in the context of animal welfare protocols areessential for maintaining highly productive bulls and their long-term quality in the semen stations.